Population screening of 75- and 76-year-old men and women for silent atrial fibrillation (STROKESTOP) - Leif Friberg; Johan Engdahl; Viveka Frykman; Emma Svennberg; Lars‐Åke Levin; Mårten Rosenqvist (2012)
Atrial fibrillation (AF) is important because it is common and is a major cause of stroke unless treated with oral anticoagulant. The prevalence of AF increases with age as does the risk of stroke. At 75 years the risk from age alone is so high that current guidelines recommend anticoagulation even in the absence of other risk factors. Atrial fibrillation is often asymptomatic and only discovered by chance or when a stroke already has occurred. We have launched a major screening study for silent AF in which 25,000 Swedes aged 75 and 76 years are randomized to either participate in a screening programme using ambulant intermittent electrocardiogram (ECG) recording to detect silent AF, or act as a control group. Patients in whom AF is detected are offered cardiological examination and anticoagulant treatment according to current guidelines. The cohort and the controls will be followed prospectively for 5 years after the inclusion of the first participant. An interim analysis will be made after 3 years. Our hypothesis is that screening for AF will reduce stroke incidence in the screened population, and that this screening will prove to be cost effective. Secondary endpoints are: any thromboembolic event, intracranial bleeding, other major bleeding, first ever diagnosis of dementia, death from any cause, and a composite of these endpoints.